Shaping Medical Minds: The Power Of Formative Assessments And Feedback (International Journal of Environmental Sciences, 2025)
INTRODUCTION: Formative assessment refers to tools that identify misconceptions, struggles, and learning gaps along the way and assess how to close those gaps. In education, the term assessment refers to the wide variety of methods or tools that educators use to evaluate, measure, and document the academic readiness, learning progress, skill acquisition, or educational needs of students. OBJECTIVES: To Evaluate the effectiveness of different modes of formative assessment like MCQ, Assignment and Reflection writing, with feedback on students’ perception.METHODOLOGY: This was a Prospective, cross over study conducted among Phase 2 medical undergraduate students in department of Pharmacology. Sample size of around 105 students were recruited after considering drop outs and selection criteria. The students were grouped into 3 batches and they were explained about the different modes of formative assessments and cross over procedure. Data was entered and analysed using SPSS software version 23.0.RESULT: When comparing the mark percentage of MCQ, Reflection writing and assignment there is statistically significant difference (P=0.0001) with respect to all the topics (GP, ANS and CVS). The students scored better in Assignment and reflection writing when compared to MCQ. But, the scoring of the regular internal assessment marks has improved in all the topics when compared with MCQ mode of formative assessment. Even though the marks obtained by students in MCQ was less, 68.4% (n=73) of students preferred MCQ’s as the optimal assessment technique.DISCUSSION: It was observed that MCQ’s as a formative assessment technique was preferred by majority of the students in this study, but their performance in MCQs was less as compared to assignment and reflection writing. They preferred MCQs as it would help them training themselves in future competitive examinations. But for facing the summative theory examinations, they preferred assignment. There is also an improvement in the internal assessment marks of students who took MCQs as the mode of formative assessment.CONCLUSION: Even though MCQ can be considered as an optimal tool of formative assessment, assignment and reflection writing should also be given equal standing. The introduction of formative assessment by the NMC in medical education regulations marks a progressive step and help students identify their strengths and areas for improvement. We conclude that, students who are assessed formatively during the process have more motivation and they feel more comfortable for the summative and competitive exams. This supports the idea that formative assessment strategies will help students achieve better in summative assessment.